2016
DOI: 10.1080/13607863.2016.1232369
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of quality of life in young onset dementia – results from a European multicenter assessment

Abstract: Background: Promoting adaptation, improving well-being and maintaining an optimal quality of life (QOL) is an important aspect in dementia care. The purpose of this study was to identify determinants of QOL in young onset dementia, and to assess differences in QoL domains between people with Alzheimer's disease (AD) and frontotemporal dementia (FTD). Methods: In total 135 persons with AD and 58 persons with FTD were included from two prospective cohort studies. QOL was assessed with the proxy reported quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 53 publications
4
30
0
Order By: Relevance
“…As expected, our results showed a negative association between the amount of unmet needs and HRQoL, which is supported by previous studies [8][9][10]. In current study we mainly focused on health related outcomes, since these are considered to be important outcomes in health-economic studies and evaluations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As expected, our results showed a negative association between the amount of unmet needs and HRQoL, which is supported by previous studies [8][9][10]. In current study we mainly focused on health related outcomes, since these are considered to be important outcomes in health-economic studies and evaluations.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have shown negative associations between higher levels of needs and quality of life in people with dementia [8][9][10]. Experiencing unmet needs in day-to-day activities may also increase the risk of institutionalization as the decreasing functioning of the person with dementia poses challenges with meeting and managing increasing needs such as eating and toileting [11].…”
Section: Introductionmentioning
confidence: 99%
“…In YOD, the life stage-specific roles and responsibilities within the family, work force, and society generate other challenges and needs which may impact on perceived QOL; however, few studies have been performed on QOL in YOD. Two studies found QOL in community-dwelling people with YOD to be associated with depressive symptoms [39, 40]. A Dutch study found a generally low prevalence of NPS in young-onset AD compared to late-onset AD during a 2-year follow-up [41].…”
Section: Introductionmentioning
confidence: 99%
“…Receiving a diagnosis of YOD is often unexpected and can be a shock as the person with dementia who is suddenly having to make sense of their world, not as they have known it, but how they are yet to experience it [27,30,33]. The traditional view of people with dementia was one of a loss of self, an erosion of the mind.…”
Section: The Yod Experience and Technologymentioning
confidence: 99%